ADOPTION OF INFORMATION AND COMMUNICATION TECHNOLOGY TO ENHANCE VETERINARY PHARMACOLOGY EDUCATION IN NIGERIAN UNIVERSITIES - Adamkolo Mohammed Ibrahim; Mohammed Bashir Tijjani (Universitas Negeri Yogyakarta, 2019)
In resource-constraint countries like Nigeria, it is envisaged that the adoption of information and communication technology (ICT) in veterinary pharmacology education at university level can enhance both quality knowledge delivery and improve students’ performance as well as ICT use skills. The literature consistently demonstrates that exposure to variety of digital and online educational resources and facilities encourages critical thinking among the students and enhance their independent problem-solving capabilities. It is long overdue cost-effective and efficient technology systems suitable for e-learning and teaching in Nigerian university education system, particularly in veterinary pharmacology academic context are explored. Emphasis should be placed on audio-visual e-learning systems such as large screen computer, digital projector and whiteboard in addition to constant power supply and Wi-Fi internet service. Being a medical course, veterinary pharmacology education will be immense enhanced if digital collaborative research and education systems are provided. To achieve this objective, relevant software and applications tailored to veterinary pharmacology students’ specific needs in the e-education process are strongly recommended given the rapid innovations in the ICT sector, which is increasingly making both hardwater and software more affordable and user-friendly.Di negara-negara dengan keterbatasan sumber daya seperti Nigeria, diperkirakan adopsi teknologi informasi dan komunikasi (TIK) dalam pendidikan farmakologi veteriner di tingkat universitas dapat meningkatkan penyampaian pengetahuan yang berkualitas dan dapat meningkatkan kinerja siswa serta keterampilan penggunaan TIK. Literatur secara konsisten menunjukkan bahwa paparan berbagai sumber daya dan fasilitas pendidikan digital dan sarana melalui (online) mendorong pemikiran kritis di antara siswa dan meningkatkan kemampuan pemecahan masalah independen mereka. Hal ini sudah lama diharapkan sebagai sebuah sistem teknologi yang hemat biaya dan efisien serta cocok untuk pembelajaran e-learning dan pengajaran di sistem pendidikan universitas Nigeria, terutama dalam konteks akademik farmakologi veteriner yang dieksplorasi. Penekanannya ditempatkan pada sistem-sistem perpustakaan dengan sistem online audio-visual seperti komputer layar besar, proyektor digital dan papan tulis di samping catu daya yang konstan dan layanan internet Wi-Fi. Melalui kursus medis, pendidikan farmakologi veteriner akan mudah ditingkatkan jika penelitian kolaboratif digital dan sistem pendidikan disediakan. Untuk mencapai tujuan ini, perangkat lunak dan aplikasi yang relevan yang disesuaikan dengan kebutuhan spesifik mahasiswa kedokteran hewan dalam proses e-edukasi sangat disarankan mengingat inovasi berkembang cepat di sektor TIK, yang semakin menjadikan air keras dan perangkat lunak lebih terjangkau dan ramah pengguna.